2016
DOI: 10.1007/s12187-016-9368-0
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Time Use in Spain: Does the Parental Human Capital Matter?

Abstract: Adolescents' time use is an interesting topic for parents and policymakers. The concern arises because time allocation between productive and unproductive activities shapes the personality of children, which has important long-term consequences on their academic and employment success. Many studies conclude family environment affects how kids spend their time. The household type, the parents' characteristics and the family customs are related to the way children spend their time. An attractive issue is the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The distribution of time that adolescents spend in doing daily activities observed here is similar to what other studies have reported, (19,31,32) this could be explained by the fact that in industrialized countries the school day requires a lot of time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The distribution of time that adolescents spend in doing daily activities observed here is similar to what other studies have reported, (19,31,32) this could be explained by the fact that in industrialized countries the school day requires a lot of time.…”
Section: Discussionsupporting
confidence: 91%
“…(18) For the purposes of the present study, time use will be understood as the quantitative dimension of the adolescents' participation in different activities, that is, the time frame measured in minutes they spend in doing certain activities, and the term activity will be used to describe what they do when using their time. (19) In addition, Law et al define the activities in terms of their relation to health and quality of life as activities of daily living that have been given a particular value and meaning by any individual and any cultural society, that is, daily life is based on the participation in these activities, which in turn contributes to improving the health and well-being of people. 20There are seven types of activities (21) and each has its own subcategories, which are described in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hofferth (2010) examined how increased exposure to media at home has changed American children's study habits. Ruiz (2017) asserted that in Spain, adolescents' time allocation between productive and unproductive activities shapes their personality. Findlay et al (2010) contended that Canadian children's leisure time or unorganized physical activities contribute to their physical and mental health.…”
Section: Linking Parental Education and Children's Time Use: Planned ...mentioning
confidence: 99%
“…The study employs a double-hurdle model that jointly analyses the decision to engage in a particular activity (namely childcare, food management and religious observance) and time devoted to it. More recently, Caparrós (2017) has investigated immigrant workers' time-use in Spain, a country that has experienced a sudden and large increase in its immigrant population. In this study, important differences between immigrants and natives in the allocation of time to a broad set of categories emerge.…”
Section: Introductionmentioning
confidence: 99%